Kondisi Karang di Pulau Baranglompo dan Bone Batang Berdasarkan Tabel Kesehatan Karang - Muh. Nurdin; Magdalena Litaay; Dody Priosambodo; Willem Moka (Jurnal Ilmu Alam dan Lingkungan, 2019)
The structure of wing scales in four species of papilionid butterflies were The research about the condition of coral reefs in Baranglompo and Bone Batang island was conducted in January to April 2016 based on “Coralwatch” table. The aim of this study was to determine health condition of coral reefs in Baranglompo and Bone Batang island. The data was obtained in the south, west, and north at a depth of 3 meters and 10 meter using Line Intercept Transect (LIT) method along 100 meters of both islands. The health condition of coral reefs was obtained from four coral colony types specifically Branching, Massive, Tabulate, and Soft coral using Coralwatch method. The results of this study showed that the health condition of coral reefs in Baranglompo and Bone Batang islands was still relatively equal. At a depth of 3 meters, the most healthy coral colony was dominated by branching corals while at a depth of 10 meters dominated by massive corals. However, the average value of coral colors indicating coral condition showed that the health condition of coral reefs in Baranglompo was higher than that in Bone Batang island. High anthropogenic impacts were observed by the trash commonly found in Baranglompo island, many fish bombings also found in Bone Batang island. This study recommend that the health condition of coral reefs in Baranglompo island was greater than that in Bone Batang island.